1972
DOI: 10.1111/j.1432-1033.1972.tb01727.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aldosterone on RNA and Protein Synthesis in the Toad Bladder

Abstract: The hypothesis of a stimulatory effect of aldosterone on RNA, and consequently protein synthesis has been investigated. The influence of this hormone on the incorporation of precursors into RNA and protein was examined in the toad urinary bladder through which sodium transport is stimulated by aldosterone in vitro.Aldosterone increases total nuclear RNA synthesis and also uridine uptake. Particular fractions of this RNA characterized by density gradient centrifugation might be specifically influenced. No effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1973
1973
1990
1990

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…(5) Well-defined labeling of all of the classes of cytoplasmic RNA was achieved with a 30-min [3H]uridine pulse and a chase of 90-150 min. Some of the earlier studies (13,14,23) used continuous labeling which may have obscured the increment in labeling of the cytoplasmic 9S-12S class imparted by the steroid. We recently found that pulse labeling 150 mim after administration of the hormone resulted in lesser incorporation of [3H]uridine into 9S-12S RNA than a similar pulse during the first 30 mim of exposure to the steroid (unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(5) Well-defined labeling of all of the classes of cytoplasmic RNA was achieved with a 30-min [3H]uridine pulse and a chase of 90-150 min. Some of the earlier studies (13,14,23) used continuous labeling which may have obscured the increment in labeling of the cytoplasmic 9S-12S class imparted by the steroid. We recently found that pulse labeling 150 mim after administration of the hormone resulted in lesser incorporation of [3H]uridine into 9S-12S RNA than a similar pulse during the first 30 mim of exposure to the steroid (unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…Precise definition of regulation of transcription by aldosterone, however, has not yet been achieved. Recent attempts to demonstrate direct effects on the synthesis of discrete classes of RNA were unsuccessful (13,14). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In concurrence with our results. Rousseau and Crabbe [20] found an increased intracellular radioactive uridine pool already 30 min after hormone applica tion. Rossier et al [19] ascertained a slight in crease after first 90 min.…”
Section: Intracellular Uridine Pool and Rna Synthesismentioning
confidence: 99%
“…After binding to a cytosolic receptor protein, the activated aldosterone/receptor complex is transferred to the nucleus [7,9]. Between the introduction of aldosterone and the first ap pearance of a physiological effect, namely the increase of Na+ transport [25], a latent period exists, ranging from 45 to 90 min [7,15,18], For this period, few biochemical data on the am phibian urinary bladder [8,20,26] and mam malian kidney [2,5,6,22] are available. In contrast, for the early and late physiological response (2-24 h), more information exists in dicating the translation of aldosterone-dependent mRNA into specific proteins, the al dosterone-induced proteins [7, 15.…”
Section: Introductionmentioning
confidence: 99%